Laparoscopic TAPP Inguinal Hernia Repair: Mesh Fixation & Peritoneal Closure by Sutural Technique - Bhuiyan, Md Jahangir Hossan; Begum, Farhana; Alam, Md Mazharul; Parveen, Urmee (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Background: The laparoscopic transabdominal preperitoneal (TAPP) inguinal repair is an evolving technique associated with well-known advantages of a minimally invasive approach. This prospective study was conducted to evaluate the feasibility, safety and effectiveness of laparoscopic TAPP using sutural mesh fixation & peritoneal closure. Intracorporeal sutural technique needs steep learning curve. Methods: Between May 2018 to December 2019, a total of 41 inguinal hernias underwent TAPP repair in 37 adults under general anesthesia. All the patients scheduled for elective inguinal hernia repair were offered the choice of the laparoscopic TAPP repair under general anesthesia. A detailed explanation of the procedure was given to all patients and informed consent was obtained. We used 2/0 vicryl for mesh fixation & peritoneal closure which took only 6.80 US Dollar in comparison to Protack from Covidien which is 167.80 US Dollar. Intraoperative & postoperative variables were recorded in pre structured proforma. Results: The 41 hernia includes 34(82.92%) direct, 07(17.08%) indirect. Unilateral hernia were 33(89.19%), & bilateral were 4(10.81%). Mean operating time for unilateral cases was 122 minutes & for bilateral 210 minutes. Mean operating time in the cases using 3D-4K image system was 70 minutes. Mean duration of hospital stay was 2.9 days. There was no conversion in this study. Postoperative complications included scrotal seroma 2(5.40%), hematoma 1(2.70%), port site infection 2(5.40%) & mesh infection 1(2.70%). Assessment of intensity of postoperative pain was evaluated according to VAS. 05 patients complained of mild pain: pain on the visual analog score (VAS) = 1-3 during one month follow-up. No patient reported with chronic pain & recurrence during the followup period. Conclusion: TAPP inguinal hernia repair with sutural mesh fixation & peritoneal closure is a feasible & safe technique with minimum postoperative morbidity and maximum patient’s satisfaction. J Bangladesh Coll Phys Surg 2023; 41: 187-192